2014
DOI: 10.1103/physrevb.90.235301
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale analysis of the GaP/Si(100) heterointerface byin situreflection anisotropy spectroscopy andab initiodensity functional theory

Abstract: A microscopic understanding of the formation of polar-on-nonpolar interfaces is a prerequisite for welldefined heteroepitaxial preparation of III-V compounds on (100) silicon for next-generation high-performance devices. Energetically and kinetically driven Si(100) step formations result in majority domains of monohydrideterminated Si dimers oriented either parallel or perpendicular to the step edges. Here, the intentional variation of the Si(100) surface reconstruction controls the sublattice orientation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 56 publications
(94 reference statements)
3
64
1
Order By: Relevance
“…7 In principle, the inversion of the GaP sublattice could also be explained by Si−P bonds combined with either (i) B-type Si(100), (ii) substitutional P adsorption or (iii) an additional Ga/P interlayer forming one ML below the uppermost Si atoms. However, these processes would then only occur during pulsed nucleation on Si cont and not on Si clean .…”
mentioning
confidence: 99%
“…7 In principle, the inversion of the GaP sublattice could also be explained by Si−P bonds combined with either (i) B-type Si(100), (ii) substitutional P adsorption or (iii) an additional Ga/P interlayer forming one ML below the uppermost Si atoms. However, these processes would then only occur during pulsed nucleation on Si cont and not on Si clean .…”
mentioning
confidence: 99%
“…Interface RA has been measured in several cases including InP=GaAsð001Þ [16], ZnSe=GaAsð001Þ and SiO 2 =Sið112Þ [17], AlAs=GaAsð001Þ [18], and GaP= Sið001Þ [5,12,13]. There have been few calculations of optical interface anisotropies.…”
mentioning
confidence: 99%
“…RA [5,12,13], LEED, XPS, and density functional theory (DFT) calculations [12,14] have shown that GaP grown on Si(001) by MOVPE has a mixed (2 × 2) and cð4 × 2Þ P dimer surface. The dimers are tilted and have a H atom on the down-tilted P atom.…”
mentioning
confidence: 99%
“…Although it has been experimentally demonstrated that the GaP/Si(001) interface is typically sharp (with a maximum interface region extension over one monolayer), it has been shown that the intermixed or terraced GaP/Si(100) interfaces atomic configurations are thermodynamically more favorable than the atomically abrupt one. Therefore, we performed the same calculations on intermixed (compensated) and terraced interfaces in order to compare the EDOS of the abrupt and hydrogenated structures with those of compensated and terraced interfaces.…”
Section: Resultsmentioning
confidence: 99%